Mathematical analysis of a metamaterial structure for Electromagnetic (EM) absorption reduction - Ahsan, Tanveer (IIUC Studies, 2022)
The rapid development of communication system such as the second generation (2G) and third-generation (3G) mobile communications, global position system (GPS), WiFi, WiMAX, wireless Bluetooth and Ultra-Wideband (UWB) systems have driven the wireless technology to a revolutionary communications. Besides, high data rate communication system has led to great demand in higher frequency next generation communication system. The wireless devices emit electromagnetic (EM) radiation during active mode of operation, which is absorbed by human body. The main challenge of the next generation communication system is to ensure safe use of wireless devices such as mobile phone.Therefore, EM radiation should be controlled towards human body. In this research, a metamaterial structure is developed and the performances of the structure is analyzed.The structure consists of a modified omega-shaped split resonator, which can manupulate behaviour of the EM wave. The mathematical analysis of the proposed antenna shows 63.29% point EM radiation reduction. IIUC Studies, Vol.-19, Issue-1, Dec. 2022, pp. 9-18